Rhyming in Kurdish modern poems (1970- 1990) - Zanyar Salih Ali; Osman Hamad Khidir Dashty (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
In the majority of studies on poetic melody and music; rhyme and rhythm are seen as the two main factors in the musicality of a poetic texts as a whole and of the lines in particular. They are regarded as the foundations of poetry's external music. The researcher will focus on them separately in this study while also keeping an eye on the emerging modern poetic styles. The reason for this is that rhythm is not as prevalent as it once was during the classical and contemporary eras. In this period, rhythm is considered an independent unit of rhyme rather than an appendix to rhyme, since the system of poetic meter and forms of this period is completely different from the poetry of previous periods of Kurdish literature. The present dissertation is a response to some of the readers and critics of this era who hold the opinion that contemporary poetry lacks rhythm and, at the same time, shows the methods of contemporary poetry.